Ossification of the posterior atlantoaxial membrane associated with atlas hypoplasia: A case report. Issue 48 (November 2016) - Meng, Yichen; Zhou, Dongxiao; Gao, Rui; Ma, Jun; Wang, Ce; Zhou, Xuhui
Abstract: Rationale: Hypoplasia with an intact posterior arch of the atlas and ossification of the posterior atlantoaxial membrane (PAAM) are individually rare. Patient concerns: The patient presented with a 6-month history of progressive weakness and paresthesia of his lower extremities. Diagnoses: Cervical myelopathy resulting from atlas hypoplasia and ossification of the posterior atlantoaxial membrane. Interventions: Laminectomy of the atlas with duroplasty. Outcomes: Preoperative symptoms were alleviated. Lessons: In most reported cases, either atlas hypoplasia or ossification of the PAAM is responsible for patients' myelopathy. The case illustrated here, to the best of our knowledge, is the first one with coexistent atlas hypoplasia and ossification of the PAAM. And laminectomy of the atlas with duroplasty provided satisfied outcome.